Parental schooling, endowment and the accumulation of specific human capital: longitudinal evidence from Thailand - Yamauchi, Futoshi; Poapongsakorn, Nipon; Ariga, Kenn (International Centre for the Study of East Asian Development, 2004)
This paper examines the effects of parents’ schooling on wages and tenure of production workers in manufacturing industries in Thailand, using micro data from a recent employee survey. Though it has been recognized in the literature that parents’ schooling, either through family education or endowment formation, influences wages, the very process has not been identified. It is found in our analysis that mother’s schooling raises child schooling and, more importantly, tenure of workers. The latter finding is not only new, but relevant to developing countries. Since a longer tenure means more accumulation of firm-specifc human capital and production experience capital, the investment in female schooling facilitates skill formation in the countries. Thus, female education has intergenerational externalities not only to schooling investments, but to the accumulation of specific human capital in manufacturing industries.